2020
DOI: 10.17221/131/2019-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence biomodulation in the management of acute traumatic wounds in two aged dogs

Abstract: Traumatic wounds represent a fairly common reason for the admission of dogs to a veterinary practice. In elderly patients, the management of wound healing can be challenging due to both the concurrent diseases and impaired physiological states, potentially resulting in delayed healing and chronic or non-healing wounds. The aim of this article is to describe an innovative therapy based on photobiomodulation (PBM) for the management of acute traumatic wounds with significant tissue loss in aged dogs. Two mixed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…With regard to the other canine skin diseases investigated in this critically appraised topic, all LLLT methods were promising in many of the included studies. In fact, in most of the articles analyzed, LLLT led to an improvement in symptoms of treated subjects and often to their complete resolution [10][11][12]16,17,20,22,[24][25][26][27][28]. In four studies (three in surgical or surgically created wounds [13][14][15] and one [19] in acral lick dermatitis), the LLLT did not show any significant clinical efficacy in the treated subjects.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…With regard to the other canine skin diseases investigated in this critically appraised topic, all LLLT methods were promising in many of the included studies. In fact, in most of the articles analyzed, LLLT led to an improvement in symptoms of treated subjects and often to their complete resolution [10][11][12]16,17,20,22,[24][25][26][27][28]. In four studies (three in surgical or surgically created wounds [13][14][15] and one [19] in acral lick dermatitis), the LLLT did not show any significant clinical efficacy in the treated subjects.…”
Section: Discussionmentioning
confidence: 93%
“…As described in Table 2, at the end of this step of quality assessment, each study was graded [32] according to total score: conclusive evidence (total score 8-10) [18,21,23], highly suggestive evidence (total score 6-7) [13,16,17,20,22], suggestive evidence (total score 4-5) [11,14,15,19,26], or inconclusive evidence (total score ≤ 3) [10,12,24,25,27,28]. Studies showing inconclusive evidence were excluded from further assessment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the treatment of bacterial infections, the effects of FLE on wound healing have been investigated in both dogs and humans. 9,[15][16][17]36,37 The primary proposed mechanism of PB in wound healing is the simulation of adenosine triphosphate (ATP) in the mitochondria. 38 Blue-green wavelengths produced during FLE also may play a role by regulating intracellular calcium.…”
Section: Discussionmentioning
confidence: 99%
“…11 These new wavelengths then interact with endogenous chromophores within bacterial cells and biological tissues to create various effects depending on the individual wavelengths. This modality has been used in veterinary medicine to treat superficial pyoderma, 12 perianal sinuses, 13 otitis externa, 14 acute traumatic wounds, 15 chronic wounds 16 and surgical wounds 17 in dogs, as well as adjunctive or sole treatment in the management of deep pyoderma 9,18,19 and interdigital pyoderma. 19,20 These studies were performed with a commercially available form of FLE which utilises a topical photoconverting hydrogel containing specialised exogenous chromophores (Phovia; Vetoquinol).…”
Section: O R I G I N a L A R T I C L E In Vitro Evaluation Of Bacteri...mentioning
confidence: 99%
“…Several studies have evaluated the effectiveness of fluorescent light energy on common dermatoses in dogs. Once or twice weekly application of FLE exerted a beneficial effect on interdigital furunculosis [10] [15], perianal fistula [14], wounds [13] and deep pyoderma [16] healing. Similarly, this study reported successful healing of 86% of dogs with FLE once a week and 14% of improvement with partial remission.…”
Section: Discussionmentioning
confidence: 99%